A promenade at Lepcis Magna: Experiencing buildings from the Augustan to the Antonine era. (November 2021) - Mugnai, Niccolò
Abstract: This article investigates the visibility of public edifices at Lepcis Magna (Lebdah, Libya) and how people in antiquity approached, lived, and experienced them. It engages with the buildings' layout, architectural and sculptural ornamentation, and epigraphic apparatuses, looking at the transformations of the cityscape from Augustus to the Antonine era. The analysis highlights the importance of private and public patronage and how social status was showcased through the monumentality and visibility of new constructions in an evolving urban environment. Buildings and their ornament drew upon a range of architectural and decorative models: influences from the centre of Empire and the Mediterranean world, long-lasting Hellenistic traditions, as well as North African and locally created, or reinterpreted, motifs that contributed to shaping the Lepcitanian architectural taste.